Watkins Family Leaving on Amtrak Train from Fresno - Watkins, Howard::::::::: (1983)
Adam Watkins holding blue umbrella stroller and small suitcase, Christine Watkins holding Robin Watkins in portable car seat in rain about to board Amtrak train Adam wearing orange hooded jacket